Cr(VI) remediation from aqueous environment through modified-TiO2-mediated photocatalytic reduction - Acharya, Rashmi; Naik, Brundabana; Parida, Kulamani (Beilstein Journal of Nanotechnology, 2018)
Cr(VI) exhibits cytotoxic, mutagenic and carcinogenic properties; hence, effluents containing Cr(VI) from various industrial processes pose threat to aquatic life and downstream users. Various treatment techniques, such as chemical reduction, ion exchange, bacterial degradation, adsorption and photocatalysis, have been exploited for remediation of Cr(VI) from wastewater. Among these, photocatalysis has recently gained considerable attention. The applications of photocatalysis, such as water splitting, CO2 reduction, pollutant degradation, organic transformation reactions, N2 fixation, etc., towards solving the energy crisis and environmental issues are briefly discussed in the Introduction of this review. The advantages of TiO2 as a photocatalyst and the importance of its modification for photocatalytic reduction of Cr(VI) has also been addressed. In this review, the photocatalytic activity of TiO2 after modification with carbon-based advanced materials, metal oxides, metal sulfides and noble metals towards reduction of Cr(VI) was evaluated and compared with that of bare TiO2. The photoactivity of dye-sensitized TiO2 for reduction of Cr(VI) was also discussed. The mechanism for enhanced photocatalytic activity was highlighted and attributed to the resultant properties, namely, effective separation of photoinduced charge carriers, extension of the light absorption range and intensity, increase of the surface active sites, and higher photostability. Advantages and limitations for photoreduction of Cr(VI) over modified TiO2 are depicted in the Conclusion. The various challenges that restrict the technology from practical applications in remediation of Cr(VI) from wastewater were addressed in the Conclusion section as well. The future perspectives of the field presented in this review are focused on the development of whole-solar-spectrum responsive, TiO2-coupled photocatalysts which provide efficient photocatalytic reduction of Cr(VI) along with their good recoverability and recyclability.
Keywords: charge transfer; Cr(VI) reduction; heterojunction; modified TiO2; photocatalysis; spinel oxides